2022
DOI: 10.1021/acs.analchem.2c01281
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Solvatochromic Proteome Stress Sensor Based on the Schiff Base Reaction

Abstract: Covalent-type probes or sensors have been seldom reported for aggregated proteins. Herein, we reported a series of covalent solvatochromic probes to selectively modify and detect aggregated proteomes through the Schiff base reaction. Such covalent modification was discovered by serendipity using the P1 probe with an aldehyde functional group, exhibiting enhanced fluorescence intensity and unusually large blue shift upon protein aggregation. Supported by the biochemical and mass spectrometry results, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…We next sought to covalently capture the aggregated proteins by anchoring reactive warheads on probe P1 and enabling proximity induced bioconjugation. We previously reported cysteine and lysine residues of the aggregated proteome can be covalently and selectively modified by aggregated proteome imaging sensors. , Encouraged by these findings, we further modulated the warheads’ reactivity to balance the selectivity and labeling kinetics. First, as the photoaffinity groups can globally label diverse amino acids via radical chemistries, we functionalized scaffold P1 with different photoaffinity groups, including benzophenone (P4), trifluoromethylphenyl diazirine (P5), and 3-hydroxy-2-naphthalenemethanol derivative (P6).…”
Section: Resultsmentioning
confidence: 99%
“…We next sought to covalently capture the aggregated proteins by anchoring reactive warheads on probe P1 and enabling proximity induced bioconjugation. We previously reported cysteine and lysine residues of the aggregated proteome can be covalently and selectively modified by aggregated proteome imaging sensors. , Encouraged by these findings, we further modulated the warheads’ reactivity to balance the selectivity and labeling kinetics. First, as the photoaffinity groups can globally label diverse amino acids via radical chemistries, we functionalized scaffold P1 with different photoaffinity groups, including benzophenone (P4), trifluoromethylphenyl diazirine (P5), and 3-hydroxy-2-naphthalenemethanol derivative (P6).…”
Section: Resultsmentioning
confidence: 99%
“…Ye 71 et al used the AggTag method to directly monitor protein oligomers, and could distinguish insoluble aggregates from other conformations in living cells. The internal polar heterogeneity of aggregates can also be quantified by a series of covalent solvent-changing probes that selectively modify and detect the aggregated proteome by Schiff base reactions 72 (Fig. 6b).…”
Section: Comparison Of Different Detection Methodsmentioning
confidence: 99%
“…This result demonstrated that NTPAN-MI (P61) not only reported on the unfolded protein located in the cytoplasm, but also, for the first time, in the nucleus. In 2022, Liu et al 109 reported another polarity sensitive probe, P5 (P62), with a reactive aldehyde moiety. Supported by the biochemical and mass spectrometry results, they have determined that the Schiff base reaction enabled this probe to selectively modify the lysine residue of aggregated proteins, instead of the folded ones.…”
Section: Polycyclic Aromatics Derivativesmentioning
confidence: 99%
“…So far, numerous polarity sensitive probes have been reported for these purposes. These works pave the way to a series of chemical strategies to design fluorescent polarity sensors for fine characterization of the heterogeneous polarity at multiple levels, from subcellular organelles like a lipid droplet or protein aggresome, , up to a living organism like the zebrafish and mouse disease model. , However, several challenges remain to be tackled by chemists when designing novel polarity sensors.…”
Section: Perspectivementioning
confidence: 99%